Airfield and Highway Pavements 2023 Testing and Characterization of Pavement Materials. - Garg, Navneet (American Society of Civil Engineers, 2023)
This collection contains 26 peer-reviewed papers on testing and characterization of pavement materials presented at the International Airfield and Highway Pavements Conference 2023, held in Austin, Texas, June 14-17, 2023.
Keywords: elektronické knihy; electronic books